(untitled) (Ordia Prima, 2025)
The manuscript tradition of Calpurnius Siculus is divided mainly into two families: one of them, on which were based most editions until the beginning of the 19th century, comprises around thirty codices recentiores (known as V); the other is represented by two codices of the 15th century (NG), whose importance was stressed by modern critical editions. There is one more codex, the Parisinus 8049 (P), from the XIIth or XIIIth century, whose place in the stemma is still under discussion: some philologists derive it from the same family as the codices recentiores, while others consider it as a third branch of the tradition. According to Reeve (1978:229-230), the answer to this question relies on the explanation of two variants. In this paper, I aim at discussing one of them. In Calpurnius’ third eclogue, Lycidas, who has been left by his lover Phyllis after a violent quarrel, tries to recover her by means of a love letter. At the end of the letter, fearing that his lover may replace him by his rival Mopsus, the shepherd threatens to commit suicide and fantasizes about a funerary epigram (vv. 90-91), which in different modern editions takes the following form: Credere, pastores, levibus nolite puellis; / Phyllida Mopsus habet, Lycidan habet ultima rerum. The text raises some critical problems, among them, in the first verb of v. 91, the variant habet NG / amat VP. In my view, the manner in which the love relationship is characterized along the whole poem supports the correction of amat. Accordingly, this reading is not to be considered a conjunctive error.